Przeobrażenia w posłudze polskich braci oblatów na misjach w świetle artykułów publikowanych w dwumiesięczniku „Misyjne Drogi” - Wrzos, Marcin (Annales Missiologici Posnanienses, 2016)
The article analyzes the contents of the review „Misyjne Drogi”, published by the Polish MIssionary Oblates of Mary Immaculate, with special focus on the theme of Oblate Brothers and their participation in missionary works of the Congregation. The changing image of the ministry of brothers is described according to three periods: 1983-1994, 1995-2011, 2012-2015. The articles published during the first period spoke mostly about brothers performing auxiliary tasks of farmer, construction worker, nurse etc. As the years passed, the authors have focused more on the direct participation of Oblate brothers in the ministry of evangelisation, on equal terms with Oblate priests.